DI PERSIMPANGAN JALAN ANTARA MELANJUTKAN PERCERAIAN ATAU MEMILIH RUJUK PADA MASA IDDAH - idham kholid (UIN Siber Syekh Nurjati Cirebon, 2016)
AbstractIslam views marriage as sacred, serious, should not be playful or temporary. Considering how the urgency of marriage, Islam sees it as things that must be maintained. However, Islam does not turn a blind eye to the reality that there are times when a household has various problems that must be going through a divorce. In Islam divorce has principles and measures are